Postoperative chylous ascites successfully managed by selective lymphatic embolization: Case report and literature review - Nguyen Ngoc Cuong, PhD; Nguyen Thanh Van Anh, PhD; Le Tuan Linh, PhD; Tran Quoc Hoa, PhD (Radiology Case Reports)
Postoperative chylous ascites is a rare complication following retroperitoneal surgeries, presenting significant challenges in diagnosis and management. Retroperitoneal cyst surgery resulting in chylous leaks is an uncommon complication that has not been previously reported in the literature. Therefore, we report a clinical case of postoperative chylous ascites following retroperitoneal cyst removal with underlying idiopathic thoracic duct obstruction. This case report details the clinical features and imaging characteristics, as well as provides insights into the diagnosis of chylous leaks and the management of selective embolization of the lymphatic branches in the lumbar region.